2019
DOI: 10.1039/c9cp01985e
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant mediated particle aggregation in nonpolar solvents

Abstract: Aggregation behavior of particles in nonpolar medium is studied with time-resolved light scattering. At low concentrations of surfactant particles are weakly charged and suspensions are not stable. Suspensions get progressively more stable with increasing surfactant concentration as particles get more highly charged. At high concentrations the particles get neutralized and aggregation is again fast. The theory of Derjaguin, Landau, Verwey, and Overbeek (DLVO) is able to predict the stability ratios quantitativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To elucidate the influence of surfactant adsorption on the aggregation behavior of nanoparticles, Farrokhbin et al dispersed three types (amidine latex, silica, and sulfate latex) of nanoparticles in non-polar solvent (decane) and added an anionic surfactant (SDS) and assessed the parameters for aggregation based on the DLVO theory (shielding distance, surface charge, and van der Waals force). 69 As a result, they reported an increase in inhibition of aggregation and stabilization of dispersion in a concentration-dependent manner until the concentration of anionic surfactant in the system reached a certain concentration. Espinosa et al also reported that the dispersion of poly (methyl methacrylate) nanoparticles was stabilized in non-polar solvents (hexane) when a nonionic surfactant (sorbitan trioleate, also named as Span 85) was present in the system.…”
Section: Surfactant-coated Nanoparticlesmentioning
confidence: 98%
“…To elucidate the influence of surfactant adsorption on the aggregation behavior of nanoparticles, Farrokhbin et al dispersed three types (amidine latex, silica, and sulfate latex) of nanoparticles in non-polar solvent (decane) and added an anionic surfactant (SDS) and assessed the parameters for aggregation based on the DLVO theory (shielding distance, surface charge, and van der Waals force). 69 As a result, they reported an increase in inhibition of aggregation and stabilization of dispersion in a concentration-dependent manner until the concentration of anionic surfactant in the system reached a certain concentration. Espinosa et al also reported that the dispersion of poly (methyl methacrylate) nanoparticles was stabilized in non-polar solvents (hexane) when a nonionic surfactant (sorbitan trioleate, also named as Span 85) was present in the system.…”
Section: Surfactant-coated Nanoparticlesmentioning
confidence: 98%
“…When the size and electrical charge are evaluated together, it can be said that a high electrical charge prevents aggregation and retention in the sand filter [49]. The lower stability observed for lower concentrations can be related to the lower magnitude of the particles' ζ potentials [50].…”
Section: Effect Of the Npls Surface Propertiesmentioning
confidence: 99%
“…Farrokhbin et al. studied the aggregation behavior of aqueous suspensions of two types of silica particles, with and without surfactant coatings, in nonpolar media [119] . The solution was treated by Aerosol‐OT (trade name of Fischer Scientific) in n ‐decane solvent and measured the agglomeration kinetics through electrophoretic mobility, zeta potential.…”
Section: Importance and Application Of Zeta Potentialmentioning
confidence: 99%